New spectroscopic and polarimetric observations of the A0 supergiant HD 92207 - Hubrig, S. (2015)
Our recent search for the presence of a magnetic field in the bright earlyA-type supergiant HD92207 using FORS2 in spectropolarimetric mode revealed thepresence of a longitudinal magnetic field of the order of a few hundred Gauss.However, the definite confirmation of the magnetic nature of this objectremained pending due to the detection of short-term spectral variabilityprobably affecting the position of line profiles in left- and right-handpolarized spectra. We present new magnetic field measurements of HD92207obtained on three different epochs in 2013 and 2014 using FORS2 inspectropolarimetric mode. A 3sigma detection of the mean longitudinal magneticfield using the entire spectrum, <B_z>_all=104+-34G, was achieved inobservations obtained in 2014 January. At this epoch, the position of thespectral lines appeared stable. Our analysis of spectral line shapes recordedin opposite circularly polarized light, i.e. in light with opposite sense ofrotation, reveals that line profiles in the light polarized in a certaindirection appear slightly split. The mechanism causing such a behaviour in thecircularly polarized light is currently unknown. Trying to settle the issue ofshort-term variability, we searched for changes in the spectral line profileson a time scale of 8-10min using HARPS polarimetric spectra and on a time scaleof 3-4min using time series obtained with the CORALIE spectrograph. Nosignificant variability was detected on these time scales during the epochsstudied.